Overview af Financial And Non-Financial Incentives for Brownfield Redevelopment - Bianca COBÂRZAN (Transylvanian Review of Administrative Sciences, 2008)
The paper addresses the intervention alternatives available for brownfield redevelopment and provides some evidence on their efficiency and impacts for different types of brownfield sites. The paper considers a number of alternatives ranging from regulatory relief, direct financial support and constraints on new redevelopments, and it attempts to identify those incentives that are the most effective means of attracting private investments to such sites. In this respect, the paper has an integrative perspective of the available alternatives for brownfield redevelopment because it analyzes financial as well as non-financial incentives. More over, the paper attempts to break the traditional strategies of economic interventions in brownfield redevelopment by analyzing the concepts of space pioneers, alternative investors and temporary uses, as alternative means for the redevelopment of sites that have little or no market value even after remediation.